2019
DOI: 10.3390/jcm8010125
|View full text |Cite
|
Sign up to set email alerts
|

Total Reference Air Kerma is Associated with Late Bowel Morbidity in Locally Advanced Cervical Cancer Patients Treated with Image-Guided Adaptive Brachytherapy

Abstract: No dose volume parameter has been identified to predict late bowel toxicities in locally advanced cervical cancer (LACC) patients treated with image-guided adaptive brachytherapy. We examined the incidence of bowel toxicities according to the total reference air kerma (TRAK) in 260 LACC patients. In both univariate and multivariate analysis, late morbidity positively correlated with a TRAK ≥2 cGy (centigray) at 1 meter, emphasizing the importance of this parameter in term of late bowel morbidity. Objective: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…and Patient 2 (16.5 cc.). Mean (SD) TRAK (total reference air-kerma rate at 1 m) was also acceptable/low at 0.0034 Gy (0.0016) and well within the 0.02 Gy associated with significant late bowel morbidity by Bockel et al [ 45 ].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…and Patient 2 (16.5 cc.). Mean (SD) TRAK (total reference air-kerma rate at 1 m) was also acceptable/low at 0.0034 Gy (0.0016) and well within the 0.02 Gy associated with significant late bowel morbidity by Bockel et al [ 45 ].…”
Section: Resultsmentioning
confidence: 63%
“…TRAK (≥ 0.02 Gy), residual HRCTV (> 25 cc. ), and prior “active smoking” have been identified as risk factors for emergent bowel toxicity in a large multivariate analysis by Bockel et al [ 45 ]. Although a prior tobacco smoker (10–20 pack-years), her EBRT was well within EMBRACE dose-volume D95 guidelines for extended-field radiation therapy (< 3500 cc): PTV V43Gy (2407.3 cc).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant correlation between ISV and GI toxicity. In previous studies, which have reported significant correlation [ 10 , 11 , 12 ], ISV or TRAK and toxicity correlation may have been confused by the dose outside target, not the whole dose volume.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective series of 642 cervical cancer cases, a dose volume defined by the half product of height, width, and thickness (HWT), demonstrated significant correlations with rectal and soft tissue complications [ 10 ]. Total reference air kerma (TRAK), on which ISVs are based, was shown to correlate with morbidity [ 11 , 12 ]. For ISV, a large retrospective study of 1,253 patients failed to demonstrate any correlation between 60 and 160 Gy ISVs and tumor control [ 13 ].…”
Section: Purposementioning
confidence: 99%
“…The continuous development of novel cancer treatments has led to an increase in the use of brachytherapy (also known as internal radiation therapy), as a complementary technique to conventional surgery approaches, such as chemotherapy and radiotherapy. This approach has been used in the treatment of a variety of malignant tumors, such as bladder cancer, cervical carcinoma, oral cancer and lung cancer [6][7][8][9][10] . At present, I-125 seeds are used in numerous applications due to a high killing radius and relative biological effect.…”
Section: Introductionmentioning
confidence: 99%